2023
DOI: 10.15244/pjoes/161876
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Impacts of Climate Change on Habitat Suitability of Three Endemic Plant Species in Pakistan

Abstract: The use of species distribution modelling under climate change to anticipate alterations in species' habitats is a concern in ecological conservation. This research aimed to simulate the present suitable habitat distribution of three species that are rare and endemic to Pakistan and to analyse the possible climate change consequences on habitat suitability in the future (2050 and 2070). We projected potentially suitable habitat distributions using two shared socioeconomic pathways scenarios (SSPs 245 and SSPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…However, the adaptive capacity of different species to extreme climate change differs, leading to significant differences in their habitat ranges under distinct climate change scenarios [39,59]. Qazi et al [60] showed that compared to SSP2-4.5, the areas of suitable zones of the shrub Buxus papillosa C.K.Schneid. (Euphorbiales: Buxaceae) and the Indian gentian Gentiana kurroo Royle (Gentianales: Gentianaceae) decreased in Pakistan under the SSP5-8.5 scenario (2070s), whereas the area of suitable zones of the shrub Rydingia limbata (Benth.)…”
Section: Changes In Suitable Habitat For S Senegal In Pakistanmentioning
confidence: 99%
“…However, the adaptive capacity of different species to extreme climate change differs, leading to significant differences in their habitat ranges under distinct climate change scenarios [39,59]. Qazi et al [60] showed that compared to SSP2-4.5, the areas of suitable zones of the shrub Buxus papillosa C.K.Schneid. (Euphorbiales: Buxaceae) and the Indian gentian Gentiana kurroo Royle (Gentianales: Gentianaceae) decreased in Pakistan under the SSP5-8.5 scenario (2070s), whereas the area of suitable zones of the shrub Rydingia limbata (Benth.)…”
Section: Changes In Suitable Habitat For S Senegal In Pakistanmentioning
confidence: 99%